Makna Stilasi Corak Motif Batik Tanjungbumi Madura - Lulus Sugeng Triandika (Studi Budaya Nusantara, 2021)
Tanjungbumi is one of the batik making areas in Madura. Batik Tanjungbumi until now still uses motif patterns for generations. Pattern motif in batik motif is a cultural heritage that has various interpretations of meaning as the background. various patterns of batik motifs are very interesting to be studied as a process and cultural products. Although Tanjungbumi Batik has a characteristic use of plant and animal symbols in its motif pattern. But in Tanjungbumi batik the representation of plant and animal symbols is done by stilation process. It is interesting to be studied more deeply to know how the representation of animal and plant symbols in Tanjungbumi batik pattern. Although there have been many studies on batik, but there is still little discussion of the value and meaning in the pattern of the motif. Moreover, the study of Tanjungbumi batik motif pattern from the perspective of semiotics analysis. This study uses qualitatively discrete methods, with data collection techniques through observation, literature studies, and interviews with resource persons. Charles Sanders Peirce's visual semiotics analysis was used to examine the object of research, namely batik pattern. Then conclusions are drawn based on data analysis.